O céu dos Tukano na escola Yupuri: construindo um calendário dinâmico - Cardoso, Walmir Thomazi (2007)
In this work I will show as I constructed, with the Brazilian Tukano Indians, a different concept in relation to the traditional calendars. The stellar dynamic calendars are constituted of circles with representations that if relate with the constellations observed in the Sky. Thus, to reach the objective to construct the dynamic calendars I studied the Tukano constellations and I used techniques of angular measures using the hands with students at Scholl Tukano Yupuri. I constructed with the students of the School Tukano Yupuri a notebook of constellations that served like a base for inquiries concerning the conceptions of this people, regarding the relations between the Nature and the constellations positions. The aboriginal constellations of the Tukano are associates with meteorological phenomena, the vegetal world, the animal world, and spiritual world also. In this study the tradition of the culture of the old aboriginals was congregated to the inquiries of the students to produce the stellar dynamic calendars. This is one of the points stronger than they associate this work with the Ethnomathematics Program